Weakly electric fish learn both visual and electrosensory cues in a multisensory object discrimination task. Issue 3 (October 2016) - Dangelmayer, Sandra; Benda, Jan; Grewe, Jan
Highlights: Fish were trained in a discrimination task involving vision and electroreception. Electrosense dominates over vision. Visual information is still memorized and used to guide behavioral decisions. Rewarded combination is preferred but also the non-rewarded cues are learned. Abstract: Weakly electric fish use electrosensory, visual, olfactory and lateral line information to guide foraging and navigation behaviors. In many cases they preferentially rely on electrosensory cues. Do fish also memorize non-electrosensory cues? Here, we trained individuals of gymnotiform weakly electric fish Apteronotus albifrons in an object discrimination task. Objects were combinations of differently conductive materials covered with differently colored cotton hoods. By setting visual and electrosensory cues in conflict we analyzed the sensory hierarchy among the electrosensory and the visual sense in object discrimination. Our experiments show that: (i) black ghost knifefish can be trained to solve discrimination tasks similarly to the mormyrid fish; (ii) fish preferentially rely on electrosensory cues for object discrimination; (iii) despite the dominance of the electrosense they still learn the visual cue and use it when electrosensory information is not available; (iv) fish prefer the trained combination of rewarded cues over combinations that match only in a single feature and also memorize the non-rewarded combination.